2009
DOI: 10.1371/journal.pone.0008402
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in Rab Escort Protein 1 (REP-1) Affect Intracellular Transport in Fibroblasts and Monocytes of Choroideremia Patients

Abstract: BackgroundChoroideremia (CHM) is a progressive X-linked retinopathy caused by mutations in the CHM gene, which encodes Rab escort protein-1 (REP-1), an escort protein involved in the prenylation of Rabs. Under-prenylation of certain Rabs, as a result of loss of function mutations in REP-1, could affect vesicular trafficking, exocytosis and secretion in peripheral cells of CHM patients.Methodology/Principal FindingsTo evaluate this hypothesis, intracellular vesicle transport, lysosomal acidification and rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 60 publications
0
34
0
1
Order By: Relevance
“…Consistent with multiple trafficking defects in the development of CHM, reduced lysosomal acidification and secretion of cytokines have been detected in monocytes isolated from CHM patients [8] and there is reduced melanosome movement into the apical processes of RPE cells in mouse models of CHM [9]. Furthermore cultured RPE cells acutely depleted of REP1 exhibit reduced lysosome acidification and delayed phagosome degradation [10].…”
Section: Introductionmentioning
confidence: 76%
“…Consistent with multiple trafficking defects in the development of CHM, reduced lysosomal acidification and secretion of cytokines have been detected in monocytes isolated from CHM patients [8] and there is reduced melanosome movement into the apical processes of RPE cells in mouse models of CHM [9]. Furthermore cultured RPE cells acutely depleted of REP1 exhibit reduced lysosome acidification and delayed phagosome degradation [10].…”
Section: Introductionmentioning
confidence: 76%
“…In the neutral pH outside and inside the cell, the light emission by pHrodo conjugated E. coli is dim and barely detectable by the fluorescent microscope or flow cytometry analysis (FACS). Once pHrodo™ dye labeled-E. coli particles are engulfed, the acidic environment within the phagolysosome causes a significant increase in fluorescent emission by the particles [19,20]. Confocal microscopy observations showed that the presence of fluorescent pHrodo inside of the phagolysosomes in the control group ( Fig.…”
Section: Skandf 96365 Inhibits the Phagocytic Ability In Peritoneal Macmentioning
confidence: 92%
“…Since only one silent single-nucleotide polymorphism has been reported in the CHM coding region, it is conceivable that missense mutations may give rise to a phenotype distinct from CHM or they may be lethal, or they may even not be disadvantageous. To date, only two nucleotide changes that could produce missense variants have been found in CHM patients, one was actually a splicing alteration [Beaufrère et al, 1999], whereas the other one substitutes Leu 550 of REP1 with a proline Strunnikova et al, 2009]. No in vitro functional analysis of this REP1 variant was performed.…”
Section: Analysis Of the Ph507r Missense Variantmentioning
confidence: 99%